Culprit and Nonculprit Recurrent Ischemic Events in Patients With Myocardial Infarction: Data From SWEDEHEART (Swedish Web System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies). Issue 1 (4th January 2018) - Varenhorst, Christoph; Hasvold, Pål; Johansson, Saga; Janzon, Magnus; Albertsson, Per; Leosdottir, Margret; Hambraeus, Kristina; James, Stefan; Jernberg, Tomas; Svennblad, Bodil; Lagerqvist, Bo
Abstract : Background: Long‐term disease progression after myocardial infarction (MI) is inadequately understood. We evaluated the pattern and angiographic properties (culprit lesion [CL]/non‐CL [NCL]) of recurrent MI (re‐MI) in a large real‐world patient population. Methods and Results: Our observational study used prospectively collected data in 108 615 patients with first‐occurrence MI enrolled in the SWEDEHEART (Swedish Web System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies) between July 1, 2006 and November 29, 2014. During follow‐up (median, 3.2 years), recurrent hospitalization for MI occurred in 11 117 patients (10.2%). Of the patients who underwent coronary angiography for the index MI, a CL was identified in 44 332 patients. Of those patients, 3464 experienced an re‐MI; the infarct originated from the NCL in 1243 patients and from the CL in 655 patients. In total, 1566 re‐MIs were indeterminate events and could not be classified as NCL or CL re‐MIs. The risk of re‐MI within 8 years related to the NCL was 0.06 (95% confidence interval [CI], 0.05–0.06), compared with 0.03 (95% CI, 0.02–0.03) for the CL. There were no large differences in baseline characteristics of patients with subsequent NCL versus CL re‐MIs. Independent predictors of NCL versus CL re‐ MI were multivessel disease (odds ratio, 2.29; 95% CI, 1.87–2.82), male sex (odds ratio, 1.36; 95% CI, 1.09–1.71), and a prolonged time between the index and re‐MI (odds ratio, 1.16; 95% CI, 1.10–1.22). Conclusions: In a large cohort of patients with first‐occurrence MI undergoing percutaneous coronary intervention, the risk of re‐MI originating from a previously untreated lesion was twice higher than the risk of lesions originating from a previously stented lesion. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT03099395.